Advances in conceptual modeling : ER 2020 Workshops CMAI, CMLS, CMOMM4FAIR, CoMoNoS, EmpER Vienna, Austria, November 3-6, 2020 proceedings (Switzerland : Springer, 2020)
This book constitutes the refereed proceedings of five workshops symposia, held at the 39th International Conference on Conceptual Modeling, ER 2020, which were supposed to be held in Vienna, Austria, in November 2020, but were held virtually due to the COVID-19 pandemic instead. The 20 papers promote and disseminate research on theories of concepts underlying conceptual modeling, methods and tools for developing and communicating conceptual models, techniques for transforming conceptual models into effective implementations, and the impact of conceptual modeling techniques on databases, business strategies and information systems. The following workshops are included in this volume: First Workshop on Conceptual Modeling Meets Artificial Intelligence and Data-Driven Decision Making (CMAI); First International Workshop on Conceptual Modeling for Life Sciences (CMLS); Second Workshop on Conceptual Modeling, Ontologies and (Meta)data Management for Findable, Accessible, Interoperable and Reusable (FAIR) Data (CMOMM4FAIR); First Workshop on Conceptual Modeling for NoSQL Data Stores (CoMoNoS); and Third International Workshop on Empirical Methods in Conceptual Modeling (EmpER).
También disponible en formato EPUB